The Influence of the Modified Free Inquiry Learning Model on Students' Critical Thinking Skills in Science Learning in Elementary Schools - Tambunan, Mullop; Remigius Abi, Antonius; Sofia Tanjung, Darinda; Sipayung, Regina; Janson Silaban, Patri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to determine the effect of the Modified Free Inquiry learning model on students' critical thinking skills in the subject of Science in grade IV of SD Negeri 097820 Bah Jambi in the 2023/2024 Academic Year. The independent variable in this study is the Modified Free Inquiry learning model (X) and the dependent variable in this study is students' critical thinking skills (Y). The research method used is an experimental method with a quantitative research type and the number of samples in this study is 25 students based on the Saturated Sampling technique. The research instrument is a questionnaire, a multiple-choice test instrument. The results of students' critical thinking skills show an average pretest of 64.84 while the average posttest value is 82.80 and for the questionnaire students get an average value of 90.24. Furthermore, the hypothesis tester shows that the t count is 6.599 while the t table is 2.069, it is proven that the hypothesis is greater, so Ho is rejected and Ha is accepted. With a determination coefficient value of 0.65, it can be explained that students' critical thinking is 65% determined by the magnitude of the modified free inquiry learning model and 35% is caused by other factors not examined in this study. Based on this, it shows that there is an influence between the Modified Free Inquiry learning model and students' critical thinking skills.